Language Strategies to Children’s Ideology in Thai Language Textbooks in Elementary Level - Thepsutham, Ansuree; Thipdet, Uamporn; Vivattanaseth, Premvit (Trends of Humanities and Social Sciences Research, 2023)
The textbook of basic Thai language elementary level According to the Basic Education Core Curriculum B.E. 2551. It is a model that aims to convey the ideas and images of children with desirable characteristics. It is worth following which will lead to being a good people of society and a good citizen of the country. There are 3 things, good children are good people of society and good citizens of the country, good children are desirable and bad children are undesirable, and behavioral characteristics of good children should be done and behavioral characteristics of bad children should not be done. There are 8 linguistic strategies for presenting ideas and images, consisting of: Lexical choices, Modality, Referencing, Reasoning, Rhetorical, Presupposition, Multivoicedness and Topics. Which such linguistic strategies, clearly conveys the ideals of the good children and bad children.